Competency Assessment of the Farmers on the Application of One House One Farm Approach (Progressive Agriculture, 2014)
The purposes of the study were to determine the extent of competency of the farmers on the application of One House One farm approach and to find out the relationships between the extent of competency of the farmers and their selected characteristics. Data were collected from 100 randomly selected farmers (out of 700) from two unions of Mymensingh Sadar Upazila. A pre-tested and structured interview schedule was used to collect data from the farmers during the period of 18 March to 01 April 2013. The extent of competency of the farmers on the application of One House One Farm approach was the dependent variable of the study. To measure the dependent variables, a total of 18 statements about competency of the farmers were selected and each of the competency was put against a four point rating scale such as excellent, above average, average and not at all, and the corresponding score were given as 3, 2, 1, and 0, respectively. Therefore, the possible range of score of 20 competencies would be 0-54. The competency gaps of the farmers were measured by Cut-Score method on rating scale. One hundred (100) is the Cut-Score with an assumption if all the respondents go for Average (score: 1). The independent variables, however, were measured by using suitable scales and techniques. Pearsons Product Moment Correlation Coefficient (r) was used to explore the relationships between the concerned variables. The findings indicate that majority of the respondents (94 per cent) had medium competency compared to 2 per cent of them having high competency. On the other hand, there were 4 respondents under low extent of competency. Out of ten selected characteristics, the farmers level of education, farm size, training exposure, extension media contact, agricultural knowledge and awareness on One House One Farm approach showed significant positive relationships with their extent of competency on the application of One House One Farm approach. Age, household size, annual family income, and organizational participation had no relationships with their extent of competency on the application of One House One Farm approach.DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19181 Progress. Agric. 24(1&2): 291 - 299, 2013